REDUPLIKASI NOMINA DAN VERBA DALAM MASYARAKAT PAKKADO’ DI SULAWESI BARAT - Nirwan; Suliadi; Uun Auliaus Sakinah (Universitas Warmadewa, 2024)
This study discusses the reduplication pattern in Pakkado' society by taking verbs and nouns as the main attention of discussion. Particularly, focus on reduplicative data. The aim is to document reduplicative words found in society. The morphological process in the form of reduplication in Pakkado' society is interesting because it shows a change in the meaning of the verbs and nouns that undergoe a reduplication process. Specifically, this study looks at the forms and meanings of reduplicated verbs and nouns. Pakkado' is a lingual category that indexes a society that calls pronouns ‘I’ as kado’. The research data found that the reduplication of words, both full and partial, had implications for the emergence of additional meanings that were slightly different from the meaning of the basic words. In the Pakkado’ society, reduplication means adding the spesific meaning to reduplicated words, that’s called a creativity of using language—this is a poectic aspect of morphology.